To improve quality in R&D, improve the team work process - Spain, David R.
David R. Spain describes how Amoco Production Research builds quality into its technology acquisition, generation, transfer, and utilization activities.
'Deliberation analysis' has proven to be a viable and valuable tool for improving quality at Amoco Production Research
The technology of knowledge work is often intangible in nature, embedded in the heads of specialists, making process improvement in R&D a unique challenge. However, key learnings from socio-technical systems design and organizational development are being integrated into team work processes at Amoco Production Research to ensure that quality is built into at least three key areas : technology acqusition and generation, technology transfer and technology utilization. Emphasis on defining and measuring performance and variance as they relate to non-linear processes has forced the organization to incorporate "deliberation analysis" into its quality tool kit. Enhanced technology and group processes (cognitive mapping tools) have facilitated analysis of Amoco's existing technology system and project portfolio, and are helping to improve quality and customer focus, while driving organizational changes needed to support our business unit clientele.
Keywords: R&D.